2023
DOI: 10.1111/jfb.15606
|View full text |Cite
|
Sign up to set email alerts
|

A review of conservation status of freshwater fish diversity in China

Liang Cao,
Wei‐Han Shao,
Wen‐Jing Yi
et al.

Abstract: China harbors a high species diversity of freshwater fishes not shared with any of its neighboring nations. Freshwater fish diversity in the country has been under severe threat from human activities over the past decades, thus conservation freshwater fishes and ecosystems is urgently needed. To accumulate baseline data for guiding protection actions, the third red list assessment of Chinese freshwater fishes was carried out. Among Chinese freshwater fishes assessed, there are 355 at‐risk species (22.3% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…However, knowledge of the ecology and conservation status of freshwater fishes is lower than that of terrestrial groups due to a bias in conservation research towards charismatic species. The diversity of freshwater fish has been severely threatened by human activities in recent decades, making the conservation of freshwater fish and their ecosystems an urgent priority (Cao et al, 2023). The conservation of fish and their habitats has received very little attention compared to other vertebrates (Maitland, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…However, knowledge of the ecology and conservation status of freshwater fishes is lower than that of terrestrial groups due to a bias in conservation research towards charismatic species. The diversity of freshwater fish has been severely threatened by human activities in recent decades, making the conservation of freshwater fish and their ecosystems an urgent priority (Cao et al, 2023). The conservation of fish and their habitats has received very little attention compared to other vertebrates (Maitland, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The third Red List assessment of Chinese freshwater fishes was conducted recently with the results published by Zhang and Cao (2021); the checklist was updated but with limited case studies and no recommendations for the conservation of freshwater fishes. Cao et al (2024) provided an overview of species diversity and their status based on the work of Zhang and Cao (2021), and they highlighted the challenges in attempts to conserve Chinese freshwater fishes using case studies and suggestions to improve the conservation of freshwater ecosystems, thereby fishes. Functional biodiversity and the impact of exotic species in local ecosystems have rarely been evaluated thoroughly in China at a riverine scale.…”
mentioning
confidence: 99%
“…Lin et al (2024) conducted a case study using a schemed mechanistic model to reveal the impacts of exotic species on functional diversity in the Minjiang River, the largest river in southeastern China, and the study suggested that exotic species altered the endemic fish community significantly if they accounted for 2% of the total species in the ecosystem. About 1591 freshwater fish species were recorded in China up until the end of 2020, and about 20 new species have been described annually (Cao et al, 2024). However, both numbers must be an underestimate, especially for the rare endemic species in upstream areas of rivers that are the most remote.…”
mentioning
confidence: 99%